Transportation of Ukrainian prisoners-of-war and internees from Eastern Galicia to the Polish POW camps in years 1918–1920 - Węglewicz, Wiktor (Narzędzia wojny, 2023)
In the years 1918–1921, one of the main challenges of Polish military logistics was the transportation of prisoners-of-war and internees from the front to camps located inside the country. This article will present a part of this problem, e.g., the transportation of the Ukrainian POWs and internees during and after the war for Eastern Galicia in 1918–1919. The following research questions will be analyzed: how was the Polish military system for POWs organized in terms of transportation? How did the POWs transfer stations in Lviv’s prison “Brygidki” and at Przemyśl-Zasanie, as well as at the assembly points at military units, function? In which conditions were prisoners-of-war transported from the front to the interior of the country?